Development of a medical education program with abdominal palpation simulators to support the understanding of traditional Japanese (kampo) medicine in beginners. Issue 3 (15th October 2019) - Arita, Ryutaro; Numata, Takehiro; Saito, Natsumi; Takayama, Shin; Togashi, Takafumi; Kaneko, Soichiro; Kikuchi, Akiko; Ohsawa, Minoru; Kamiya, Tetsuharu; Abe, Michiaki; Ishii, Tadashi
ABSTRACT: Aim: Traditional Japanese (kampo) medicine has recently been included in the medical education curriculum in Japan; hence, an education program in kampo physical examination for beginners is needed. The aim of the present study was to develop an education program using a simulator of kampo abdominal palpation that would enable beginners to acquire this skill, and to assess the effectiveness and usefulness of the education program. Methods: First, we conducted a preliminary trial. Fifteen beginners received a lecture about abdominal findings and the associated representative kampo formulas and underwent a simulator palpation test. Following this trial, we created and conducted a 1 day education program as a prospective study. The program included a general lecture on physical examination in kampo medicine, followed by a pre‐test assessment involving palpation of the simulators, a specific lecture about abdominal palpation, and finally a post‐test assessment. The pre‐ and post‐test accuracy rates were evaluated. Results: High accuracy rates were obtained in the preliminary trial, but the research protocol did not enable an assessment of the effectiveness or usefulness of the trial. In the subsequent education program, 41 participants had significantly higher accuracy rates after the lecture than before the lecture, in both abdominal findings (from 78.2% to 94.4% on average, P < 0.001) and in the associated representative kampo formulas (from 21.8% to 59.7% on average, P < 0.001). Conclusion: An education program using simulators for kampo abdominal palpation can be effective and useful for beginners in kampo medicine.